The The Relationship Between Oral Health Conditions of Pregnant Women with Accumulation of Fusobacterium nucleatum and the Risk of Low Birth Weight (LBW) - Hans Lesmana; Rini Sitanaya; Surya Irayani; Asriawal; Syamsuddin; Hansen Lesmana; Benni Benyamin; Prasko (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2026)
Various physical and physiological changes occur during pregnancy. These changes occur as the body prepares for birth and fetal development. These changes can affect systems in the body that affect the physiology of body parts, including the oral cavity. The increased risk of tooth decay occurs as a result of fear of brushing teeth due to gum conditions that can be inflamed during pregnancy. This study aims to determine the accumulation of Fusobacterium Nucleatum bacteria in the oral cavity of pregnant women on the risk of LBW (Low Birth Weight). This type of study is a prospective observational analytical ohort conducted to determine the accumulation of Fusobacterium Nucleatum bacteria in the oral cavity of pregnant women on the incidence of low birth weight. Samples were taken using the accidental sampling method to obtain 12 pregnant women in their third trimester, who were then periodically examined for the condition of their oral cavity and a 20 ml saliva sample was taken during the last week of pre-partum check-up. There was no significant relationship between the accumulation of Fusobacterium Nucleatum bacteria in the saliva of pregnant women and the incidence of LBW babies. This is because other factors contribute to the incidence of low birth weight (LBW), such as nutritional status, oral health practices, socioeconomic status, infectious diseases, and other external factors. In addition to prenatal checkups during each trimester, oral examinations are also essential. Plaque control and tartar cleaning are essential for pregnant women. Routine oral examinations are essential.